2015
DOI: 10.1039/c4cp05424e
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of the vibrational frequencies of carbon clusters and fullerenes with empirical potentials

Abstract: Vibrational frequencies for carbon clusters, fullerenes and nanotubes evaluated using empirical carbon-carbon potentials are presented. For linear and cyclic clusters, frequencies evaluated with the reactive empirical bond order (REBO) potential provide the closest agreement with experiment. The mean absolute deviation (MAD) between experiment and the calculated harmonic frequencies is 79 cm 1 for the bending modes and 76 cm 1 for the stretching modes. The effects of anharmonicity are included via second order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 62 publications
(121 reference statements)
0
7
0
Order By: Relevance
“…Semiempirical methods have recently been shown to correspond fairly well with experiments. 46,47 The vibrational density of states (VDOS) can well be used to determine many chemical and physical properties of carbon nanotubes. Besides studying chirality and defects, the VDOS can also be used to calculate thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Semiempirical methods have recently been shown to correspond fairly well with experiments. 46,47 The vibrational density of states (VDOS) can well be used to determine many chemical and physical properties of carbon nanotubes. Besides studying chirality and defects, the VDOS can also be used to calculate thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…We have assumed those multiplicities for the calculations. The calculated vibrational frequencies are listed in Table 1, together with the experimental values, given in [30]. While the lowest-energy modes are well reproduced by the calculations, some deviations are seen for the higher frequency modes.…”
Section: Level Densitiesmentioning
confidence: 83%
“…Atac et al suggested that the C�O difference between DFT and experimental can go up to 35 cm −1 differences [33]. At the same time, Do et al found the difference between the theory and the experimental goes up to 58 cm −1 for a large molecule like C 60 fullerenes (even though the molecule is highly symmetric and has no functional group other than C�C) [34].…”
Section: Discussionmentioning
confidence: 99%